Air Processed Inkjet Infiltrated Carbon Based Printed Perovskite Solar Cells with High Stability and Reproducibility. Issue 1 (7th November 2016) - Hashmi, Syed Ghufran; Martineau, David; Li, Xiong; Ozkan, Merve; Tiihonen, Armi; Dar, M. Ibrahim; Sarikka, Teemu; Zakeeruddin, Shaik Mohammed; Paltakari, Jouni; Lund, Peter. D.; Grätzel, Michael
Abstract : Carbon based perovskite solar cells are fabricated for the first time in a room temperature environment by employing inkjet infiltration of perovskite precursor ink. The fabricated perovskite solar cells exhibit impressive performance reproducibility with this automated method and exhibit high stability when exposed to 35 °C for a period of 1046 hours.